Application of Sugarcane Bagasse and Tea in Growing Media on the Growth and Yield of Red Lettuce (Lactuca sativa L. var. Crispa): Aplikasi Ampas Tebu dan Teh Dalam Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca sativa L. var. Crispa) - Sari, Adelia Dwi Ella; Nurmalasari, Intan Rohma (Procedia of Engineering and Life Science, 2023)
This study aims to determine the effect of bagasse and tea as a growing medium on the growth and yield of red lettuce (Lactuca sativa L. var. crispa). The research was carried out in January - March 2023. The study used the Randomized Block Design (RBD) method which consisted of 5 treatments with 4 replicates, each treatment consisting of 3 plants which produced 20 experimental units. The treatments included: P0 (100% soil), P1 (75% soil + 25% bagasse), P2 (75% soil + 25% tea bagasse), P3 (50% soil + 50% sugarcane bagasse), P4 (50% soil 50% + 50% tea dregs). The observed variables consisted of plant height, number of leaves, stem diameter, fresh weight per plant, dry weight per plant, and harvest index. The data were analyzed using analysis of variance (ANOVA) then followed by a 5% level honest significant difference test (BNJ). And there is the effect of a combination of tea waste growing media on plant height, plant wet weight, and harvest index of red lettuce plants.